Dopaminergic Dysregulation in Syndromic Autism Spectrum Disorders: Insights From Genetic Mouse Models - Kosillo, Polina; Bateup, Helen S. (Frontiers in Neural Circuits, 2021)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder defined by altered social interaction and communication, and repetitive, restricted, inflexible behaviors. Approximately 1.5-2% of the general population meet the diagnostic criteria for ASD and several brain regions including the cortex, amygdala, cerebellum and basal ganglia have been implicated in ASD pathophysiology. The midbrain dopamine system is an important modulator of cellular and synaptic function in multiple ASD-implicated brain regions via anatomically and functionally distinct dopaminergic projections. The dopamine hypothesis of ASD postulates that dysregulation of dopaminergic projection pathways could contribute to the behavioral manifestations of ASD, including altered reward value of social stimuli, changes in sensorimotor processing, and motor stereotypies. In this review, we examine the support for the idea that cell-autonomous changes in dopaminergic function are a core component of ASD pathophysiology. We discuss the human literature supporting the involvement of altered dopamine signaling in ASD including genetic, brain imaging and pharmacologic studies. We then focus on genetic mouse models of syndromic neurodevelopmental disorders in which single gene mutations lead to increased risk for ASD. We highlight studies that have directly examined dopamine neuron number, morphology, physiology, or output in these models. Overall, we find considerable support for the idea that the dopamine system may be dysregulated in syndromic ASDs; however, there does not appear to be a consistent signature and some models show increased dopaminergic function, while others have deficient dopamine signaling. We conclude that dopamine dysregulation is common in syndromic forms of ASD but that the specific changes may be unique to each genetic disorder and may not account for the full spectrum of ASD-related manifestations.